2014
DOI: 10.4236/jct.2014.51011
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer in Women with Inflammatory Pap Smears

Abstract: In spite of preventive measures such as Papanicolaou cervical cytological analysis and, more recently, vaccination against HPV infection, cancer of the uterine cervix continues to be one of the most frequent causes of mortality among women worldwide, particularly in developing countries. In this prospective study, sixty patients with inflammatory Pap smears had a colposcopy with directed biopsies. The average age of our patients was 42 years. Results showed that colposcopy is normal in 10% of women. It showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…22,23 Persistent inflammatory cervical smears can lead to chronic irritation and can be fertile soil for neoplastic transformation. 24 In our study the incidence of normal cervical smears is low as most of the patients were attending gynaecology clinic for some complaints and none of the patient was volunteer for cervical cancer screening. 23,24 In our study, the diagnoses of LSIL was in seven cases (6.14 %) out of total of 114 cases.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…22,23 Persistent inflammatory cervical smears can lead to chronic irritation and can be fertile soil for neoplastic transformation. 24 In our study the incidence of normal cervical smears is low as most of the patients were attending gynaecology clinic for some complaints and none of the patient was volunteer for cervical cancer screening. 23,24 In our study, the diagnoses of LSIL was in seven cases (6.14 %) out of total of 114 cases.…”
Section: Resultsmentioning
confidence: 75%
“…24 In our study the incidence of normal cervical smears is low as most of the patients were attending gynaecology clinic for some complaints and none of the patient was volunteer for cervical cancer screening. 23,24 In our study, the diagnoses of LSIL was in seven cases (6.14 %) out of total of 114 cases. This establishes the importance cervical Pap smears in diagnosing precancerous lesions of cervix.…”
Section: Resultsmentioning
confidence: 75%
“…Achour et al detected HPV-specific antibodies in sera of 60 women, with inflammatory Pap smears, of reproductive, perimenopausal and post-menopausal age group. [22] Results showed that six patients (10%) (showed a positive reactivity to at least one of the HPV-16 or HPV-18 antigens and sera showed different reactivity to the different antigens with the following percentages: 5%, 3%, 2%, 3% and 3% for L1 HPV-16, E6 HPV-16, E7 HPV-16, E6 HPV-18 and E7 HPV-18 respectively. [22] They had used GST capture ELISA for measuring anti-HPV antibodies, [22] unlike VLP L1 ELISA used in the present study.…”
Section: Evaluation Of Pap Smear and Hpvvlp Serology In Clinically Sumentioning
confidence: 99%
“…[22] Results showed that six patients (10%) (showed a positive reactivity to at least one of the HPV-16 or HPV-18 antigens and sera showed different reactivity to the different antigens with the following percentages: 5%, 3%, 2%, 3% and 3% for L1 HPV-16, E6 HPV-16, E7 HPV-16, E6 HPV-18 and E7 HPV-18 respectively. [22] They had used GST capture ELISA for measuring anti-HPV antibodies, [22] unlike VLP L1 ELISA used in the present study. They concluded that Serology is not in itself a diagnostic method but must be kept in consideration for monitoring patients with an inflammatory cervical smear.…”
Section: Evaluation Of Pap Smear and Hpvvlp Serology In Clinically Sumentioning
confidence: 99%
See 1 more Smart Citation